Corrections to "Variational adaptive correlation method for flow estimation" [Jun 12 3053-3065] - Becker, Florian; Petra, Stefania; Schnörr, Christoph (IEEE transactions on image processing, 2012)
In the above paper (ibid., vol. 21, no. 6, pp. 3053-3065, Jun. 2012), several corrections requested by the authors were omitted. The IEEE regrets the error. On pp. 3058 and 3059, the algorithms were not indented corrected. They are corrected here.
Gesehen am 30.07.2018